2020
DOI: 10.1017/s0029665120007910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary restriction on metabolic and cognitive health

Abstract: Life expectancy in most developed countries has been rising over the last century. In the UK alone, there are around 12 million people over 65 years old and centenarians have increased by 85% in the past 15 years. As a result of our ageing population, which is due mainly to improvements in medical treatments, public health, improved housing and lifestyle choices, there is an associated increase in prevalence of pathological conditions, such as metabolic disorders, type 2 diabetes (T2D), cardiovascular and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 155 publications
(318 reference statements)
0
3
0
Order By: Relevance
“…Life expectancy has been rising in most countries over the past decades, as well as the prevalence of aging-associated pathological conditions [ 50 ]. It is suggested that a long-term, low-fat, whole-food vegan diet may increase life expectancy in humans by down-regulating IGF-I activity [ 51 ].…”
Section: Methionine Restriction (Mr) Aging and Diseasesmentioning
confidence: 99%
“…Life expectancy has been rising in most countries over the past decades, as well as the prevalence of aging-associated pathological conditions [ 50 ]. It is suggested that a long-term, low-fat, whole-food vegan diet may increase life expectancy in humans by down-regulating IGF-I activity [ 51 ].…”
Section: Methionine Restriction (Mr) Aging and Diseasesmentioning
confidence: 99%
“…Increased prevalence of age-related diseases increases interest in finding nutritional interventions that could delay the onset or progression of these disorders (11). Methionine restriction (MR) has shown benefits in metabolism and longevity, by mimicking caloric restriction (CR) without promoting malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…This makes MR an attractive dietary intervention for the prevention or reversal of conditions such as obesity, type 2 diabetes, cardiovascular disease, and potentially autoimmune disorders. While most of MR's known benefits pertain to peripheral systems, new and emerging evidence suggests that MR also benefits the brain and promotes cognitive health [16]. Currently, the exact cellular mechanisms mediating MR's central benefits are widespread yet underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…autoimmune disorders. While most of MR's known benefits pertain to peripheral systems, new and emerging evidence suggests that MR also benefits the brain and promotes cognitive health [16].…”
Section: Introductionmentioning
confidence: 99%